STRATEGI PEMBELAJARAN PENJAS BERBASIS BUDAYA LOKAL BAGI PESERTA DIDIK SD DI DAERAH RAWAN BENCANA - Ubaedi Ubaedi; Aidil Putra; Rahmat Gunawan; Ilona Pratiwi Hutabarat; Wendri Maryadi (YLPK Mahardhika, 2025)
This study examines the effectiveness of local culture-based physical education learning strategies in enhancing motor development among elementary school students living in disaster-prone areas. The research was conducted at SDN 2 Banjaririgasi using a quantitative correlational design. Participants consisted of 55 fourth-grade students. Data on the implementation of local culture in physical education were collected through a validated and reliable questionnaire focusing on traditional games. Meanwhile, students’ motor development was assessed using the Motor Ability Test, which measures agility, coordination, balance, and speed. Data were analyzed using Pearson Product Moment correlation. The results revealed a very strong and statistically significant relationship between local culture-based learning strategies and students’ motor development (r = 0.972; p < 0.05). These findings suggest that integrating local cultural elements into physical education learning not only preserves cultural values but also plays a meaningful role in optimizing students’ motor skills. Therefore, local culture-based physical education strategies can serve as an effective and contextually relevant approach for supporting motor development in elementary schools located in disaster-prone regions.